2014
DOI: 10.1515/pac-2013-1111
|View full text |Cite
|
Sign up to set email alerts
|

Chemoecological studies on marine natural products: terpene chemistry from marine mollusks

Abstract: Some species of nudibranchs (Mollusca) protect themselves from predatory attacks by storing defensive terpene chemicals acquired from dietary sponges (Porifera) in specialized body parts called MDFs (mantle dermal formations), often advertising their unpalatability to potential predators by means of bright coloration patterns. Consequently, the survival of these trophic specialist species is closely related to the possibility of obtaining the defensive tools from sponges that live in their immediate vicinity; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…In addition, some known sesquiterpenes, including dendrolasin (12) (Figure 3), are found in the Patagonian doridacean Tyrinna nobilis [89]. Furthermore, (5R,6Z)-dendrolasin-5-acetate was isolated from Hypselodoris jacksoni from Australia [90]. The dendronotid slug Doto pinnatifida from the Atlantic presents dotofide (13) (Figure 3), a guanidine-interrupted terpenoid with an unknown ecological role [91].…”
Section: Monocyclic Sesquiterpenoidsmentioning
confidence: 99%
“…In addition, some known sesquiterpenes, including dendrolasin (12) (Figure 3), are found in the Patagonian doridacean Tyrinna nobilis [89]. Furthermore, (5R,6Z)-dendrolasin-5-acetate was isolated from Hypselodoris jacksoni from Australia [90]. The dendronotid slug Doto pinnatifida from the Atlantic presents dotofide (13) (Figure 3), a guanidine-interrupted terpenoid with an unknown ecological role [91].…”
Section: Monocyclic Sesquiterpenoidsmentioning
confidence: 99%
“…Here we presented an initial chemical investigation of nudibranch Hypselodoris infucata collected from Tulamben-Bali, a less-explored waters but rich in species diversity. Our research group have pioneered the chemical investigation of marine invertebrate mainly sponges and nudibranchs from this prolific site (Mańdi et al, 2015;Mudianta et al, 2014). We also reported for the first time the development of a method to assay nudibranch extracts for their feeding deterrent activity against local shrimps Penaeus vannamei.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite slow movements and the absence of physical attributes, only few predators have been documented. Chemoecological studies showed that nudibranchs may employ secondary metabolites as chemical defence mechanism against predators (Cimino and Ghiselin, 2009;Mudianta et al, 2014). The metabolites are either derived from their diets mainly sponges or biosynthesized in de novo fashion (Fontana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The feeding deterrence activity of compounds 1-3 was evaluated against the cooccurring generalist shrimp Palaemon elegans Rathke, 1837, following an approach already used to assess the palatability of other bioactive metabolites (31), including marine furanosesquiterpenes (32,33). Like other palaemonid species (34,35), P. elegans is suitable for evaluations of this kind, which require a good view of the ingested food in the digestive system (31). Given that decapod crustaceans exhibit complex learning ability (36,37), the possibility that the shrimp learn to avoid the compounds after experiencing aversive olfactory stimuli was also considered.…”
mentioning
confidence: 99%